2011
DOI: 10.1063/1.3554374
|View full text |Cite
|
Sign up to set email alerts
|

On-chip measurement of the Brownian relaxation frequency of magnetic beads using magnetic tunneling junctions

Abstract: We demonstrate the detection of the Brownian relaxation frequency of 250 nm diameter magnetic beads using a lab-on-chip platform based on current lines for exciting the beads with alternating magnetic fields and highly sensitive magnetic tunnel junction MTJ sensors with a superparamagnetic free layer. The first harmonic out-of-phase component of the MTJ response gives the imaginary part of the magnetic bead susceptibility, which peaks at the Brownian relaxation frequency. This work paves the way to on-chip imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…The method has been successfully demonstrated for the detection of bacterial DNA and spores (Zardán Gómez de la Torre et al, 2012) as well as for studies of drug resistance in Mycobacterium Tubercolosis (Engström et al, 2013). In addition to bulky laboratory AC susceptometers, the method has been demonstrated using portable AC susceptometers (Zardán Gomez de la Torre et al, 2011) and magnetoresistive sensors integrated in a microfluidic system Donolato et al, 2011;Østerberg et al, 2014;Østerberg et al, 2013). Although, these methods have provided significant substantial reductions in cost, size and integratability, they are not easily implemented in a truly low-cost system suited for single use sample analysis.…”
Section: Introductionmentioning
confidence: 97%
“…The method has been successfully demonstrated for the detection of bacterial DNA and spores (Zardán Gómez de la Torre et al, 2012) as well as for studies of drug resistance in Mycobacterium Tubercolosis (Engström et al, 2013). In addition to bulky laboratory AC susceptometers, the method has been demonstrated using portable AC susceptometers (Zardán Gomez de la Torre et al, 2011) and magnetoresistive sensors integrated in a microfluidic system Donolato et al, 2011;Østerberg et al, 2014;Østerberg et al, 2013). Although, these methods have provided significant substantial reductions in cost, size and integratability, they are not easily implemented in a truly low-cost system suited for single use sample analysis.…”
Section: Introductionmentioning
confidence: 97%
“…The Brownian relaxation frequency is directly related to the hydrodynamic radius of the beads, such that changes in the radius due to target binding at the bead surface manifest as a shift in the relaxation frequency. Dalslet et al 24 and Donolato et al 25 have recently demonstrated on-chip detection of beads suspended in a fluid above a magnetoresistive sensor based on their Brownian relaxation. However, sensitivity at the level of individual microbeads has not yet been demonstrated using such a mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This mode of sensing precludes subsequent transport of immobilized beads, and requires chemical decoration of the sensors, which adds complexity to device fabrication. Brownian relaxation biodetection 24,25,[27][28][29][30][31][32] instead uses the beads themselves as the capture agent and thus does not require chemical immobilization of beads on the sensor surface. The Brownian relaxation frequency is directly related to the hydrodynamic radius of the beads, such that changes in the radius due to target binding at the bead surface manifest as a shift in the relaxation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the features that makes SAFs extremely interesting for applications is their wide applicability to in-plane as well out-of-plane magnetized materials, their large tunability via layer thickness and material composition, and the possibility to combine SAF and exchange bias by adding an antiferromagnetic layer to the stack. Throughout the years, SAFs were successfully used in spin-valves [4,5] and magnetic tunnel junctions [6][7][8][9] as reference layers, with applications as read heads in magnetoresistive [10,11] hard drives [12], magnetic random access memories (MRAM) [13][14][15], microwave oscillators [16] and magnetic biosensors [17][18][19][20][21][22]. More recently, SAFs have been proposed as base materials for racetrack memories [23], due to the higher domain wall velocity with respect to single ferromagnetic layers [24], and their capability to host a range of topological spin-textures [25].…”
Section: Introductionmentioning
confidence: 99%